6 - Poverty Eradication Dilemma: Understanding Poverty Dynamics in Nebbi District, Uganda - Lakwo, Alfred (Africa Development, 2021)
This paper addresses a current methodological gap in poverty measurement, which stems from acknowledging the multi-dimensionality of poverty, on the one hand, and using an income/consumption measurement of poverty as the norm, on the other. The current income-based measure of poverty presents only part of measuring poverty status as a whole. The consumption basket is wrongly taken by those of economic inclination to wholly represent the entire, even non- monetary valued, range of poverty. The paper approaches this dilemma using a participatory and community-driven approach where the subjective views of people are used to define and categorize the poor, contrary to the poverty line approach. Such categorization was based on the perceived wellness of life and what made/denied wellness. A survey follows to explore the quantitative scope of poverty. This participatory, qualitative and quantitative mix of method, it is argued, provides for ascertaining organizational accountability in terms of the relevance of programme targeting and outreach as well as performance measurement over time. The method can also be used to deepen current participatory poverty assessments that simply stop at defining and identifying poverty causes, effects and solutions.